Effects of Different Swimming Exercise Intensities on Bone Tissue Composition in Mice: A Raman Spectroscopy Study - da Silva, Fabiano Fernandes; de Souza, Renato Aparecido; Tavares Pacheco, Marcos Tadeu; Ribeiro, Wellington; Souza Rodrigues da Silva, Marcos Augusto; Miranda, Humberto; Castillo Salgado, Miguel Angel [UNESP]; de Melo Castilho, Julio Cezar [UNESP]; Silveira, Landulfo (Mary Ann Liebert, Inc., 2011)
Objective: Raman spectroscopy was employed to evaluate the effect of different swimming intensities on femoral bone composition in an animal model. Background Data: Intense swimming exercise may affect bone mineralization, and Raman technique has been shown to be effective in evaluating tissue composition (phosphate minerals and carbonate apatites - bands at 960 and 1170 cm(-1), as well as collagen matrix - amide I band at 1660 cm(-1)). Materials and Methods: Eighteen female Swiss Webster mice were separated into three groups (n = 6 per group) of sedentary (SED), and swimming with an intensity of 40% (PT-40) and 80% (PT-80) of the maximum load, with 6 weeks of training. Near-infrared Raman spectra (830nm wavelength and 80mW laser power) were obtained with a dispersive Raman spectrometer using a CCD camera and imaging spectrograph with 30-s integration time. Spectra were collected in the medial and lateral diaphysis of the femur and principal components analysis (PCA) was employed to extract features of the Raman bands of bone and to perform quantitative analysis. Results: PC1 vector resembles Raman spectra and carries information about apatite minerals and some contribution from organic matrix. A statistically significant difference was found in the PC1 scores (ANOVA, p < 0.05), indicating lower mineral concentrations in the femur in both the PT-40 and PT-80 groups compared to the SED group. These results corroborated with the radiographic assessment of bone density. Conclusion: Raman technique associated with PCA statistics showed that intense swimming exercise may affect bone mineralization and remodeling in a mouse model of training.